Advanced C++ programming cookbook : become an expert C++ programmer by mastering concepts like templates, concurrency, and type deduction - Quinn, Rian (Packt Publishing, 2020)
This book is for C++ developers with a good understanding of the language and an interest in advanced language features, who want to obtain expert skills to solve recurring problems with tailormade solutions.